Global transmission of monkeypox virus—a potential threat under the COVID-19 pandemic - Wang, Yang; Leng, Ping; Zhou, Hao (Frontiers in Immunology, 2023)
Since May 2022, Monkeypox virus (MPXV) cases have dramatically increased worldwide, in both endemic and non-endemic areas. Until Feb 20rd, 2023, a total of 85,922 cases have been reported by the Center for Disease and Prevention (CDC). MPXV became a potential public threat under the COVID-19 pandemic. The transmission and prevalence of MPXV requires more close attention. In this comprehensive review, we describe the basic characteristics, transmission routes, and susceptible individuals of MPXV as well as discuss the main causes of the current outbreak. The history, clades, genetic evolution, and transmission tendency of MPXV are depicted. Regarding viral transmission analysis in several geographical spots, we would like to point out that men who have sex with men (MSM) could play important roles in the process of transmission that eventually causes viral outbreaks. Susceptible populations at high risk of infection alert society to raise awareness on the protection of these special individuals. We also highlight that airline traveling is a driving force in causing international MPXV transmission. Further summarization of the clinical implications, the prevention of MPXV, and clinical measures of viral detection can enable the rapid diagnosis of MPXV. An improved understanding of MPXV would help us take reasonable and timely diagnostic and effective measures to prevent the massive spread of MPXV during the COVID-19 pandemic from causing a new pandemic.